The Effect of Work Environment on Employee Productivity in the Banking Industry in Indonesia: A Case Study on Ergonomics, Mental Health, and Operational Efficiency - Loso Judijanto; Mislan Sihite; Ahmad Hanafie; I Dewa Gede Sayang Adi Yadnya (West Science Journal Economic and Entrepreneurship, 2023)
The present research endeavors to examine the complex interactions among ergonomics, mental health, operational efficiency, and employee productivity in the ever-changing Indonesian banking sector. 200 participants in a sample from a range of roles contributed insightful information about the complex interactions between these important factors. Confirmatory factor analysis ensured the robustness of later structural equation modeling by confirming the measurement model's validity and dependability. The findings highlighted the beneficial effects of ergonomics, mental health, and operational efficiency on employee productivity, as well as considerable direct and indirect consequences. The structural model was further validated using the model fit indices and discriminant validity analysis. The model explains a significant amount of the variance in the Work Environment, according to the R-Square values. The research provides insightful information for managers of organizations, indicating that ergonomic enhancements, mental health, and operational effectiveness interventions can all work together to create a favorable work environment and, as a result, increase worker productivity in Indonesian banks.